Transverse momentum spectra of inclusive b jets in pPb collisions at $\sqrt{s_{NN}} = $ 5.02 TeV - CMS collaboration (2311 authors) (2016)
We present a measurement of b jet transverse momentum (pT) spectra in proton-lead (pPb) collisions using a dataset corresponding to about 35 nb−1 collected with the CMS detector at the LHC. Jets from b quark fragmentation are found by exploiting the long lifetime of hadrons containing a b quark through tagging methods using distributions of the secondary vertex mass and displacement. Extracted cross sections for b jets are scaled by the effective number of nucleon–nucleon collisions and are compared to a reference obtained from pythia simulations of pp collisions. The pythia -based estimate of the nuclear modification factor is found to be 1.22±0.15(stat+syst pPb)±0.27(syst pythia) averaged over all jets with pT between 55 and 400 GeV/c and with |ηlab|<2 . We also compare this result to predictions from models using perturbative calculations in quantum chromodynamics.